Kilka uwag o stanie badań nad kompetencją słowotwórczą dzieci z niepełnosprawnością intelektualną - Marciniak-Firadza, Renata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
A description of the understanding (reception, decoding, interpretation) and creation (expression, coding) of word-building structures by children with minor intellectual disabilities, and a specification of how these word-building structures exist in the linguistic awareness of such children, is important as there exists no research and therefore no studies related to the word-building skills of children with intellectual disabilities. The only data related to word-building skills in children with intellectual disabilities available are the names of professions collected by A. Wątorek in her research on the linguistic competences responsible for the development of lexical skills. The data incorporated in the said study allowed the linguistic and wordbuilding analysis, and hence made it possible to indicate the methods of coding the names of professions/ persons performing certain activities by children with minor intellectual disabilities.